A surface structural model for ferrihydrite II: Adsorption of uranyl and carbonate - Hiemstra, Tjisse; Riemsdijk, Willem H. Van; Rossberg, André; Ulrich, Kai-Uwe (Geochimica et cosmochimica acta, 2009)
The adsorption of uranyl (UO 2 2+) on ferrihydrite has been evaluated with the charge distribution (CD) model for systems covering a very large range of conditions, i.e. pH, ionic strength, CO 2 pressure, U(VI) concentration, and loading. Modeling suggests that uranyl forms bidentate inner sphere complexes at sites that do not react chemically with carbonate ions. Uranyl is bound by singly-coordinated surface groups present at particular edges of Fe-octahedra of ferrihydrite while another set of singly-coordinated surface groups may form double-corner bidentate complexes with carbonate ions. The uranyl surface speciation strongly changes in the presence of carbonate due to the specific adsorption of carbonate ions as well as the formation of ternary uranyl-carbonate surface complexes. Data analysis with the CD model suggests that a uranyl tris-carbonato surface complex, i.e. (UO 2)(CO 3) 3 4−, is formed. This species is most abundant in systems with a high pH and carbonate concentration. This finding differs significantly from previous interpretations made in the literature. At high pH and low carbonate concentrations, as can be prepared in CO 2-closed systems, the model suggests the additional presence of a ternary uranyl-monocarbonato complex. The binding mode (type A or type B complex) is uncertain. At high uranyl concentrations, uranyl polymerizes at the surface of ferrihydrite giving, for instance, tris-uranyl surface complexes with and without carbonate. The similarities and differences between U(VI) adsorption by goethite and ferrihydrite are discussed from a surface structural point of view.